Physiological genetic variation in tomato fruit chilling tolerance during postharvest storage - David, Sivan; Levin, Elena; Fallik, Elazar; Alkalai-Tuvia, Sharon; Foolad, Majid R.; Lers, Amnon (Frontiers in Plant Science, 2022)
Storage at low temperatures is a common practice to prolong postharvest life of fruit and vegetables with a minimal negative impact on human/environmental health. Storage at low temperatures, however, can be restricted due to produce susceptibility to non-freezing chilling temperatures, when injuries such as physiological disorders and decays may result in unmarketable produce. We have investigated tomato fruit response to postharvest chilling stress in a recombinant inbred line (RIL) population developed from a cross between a chilling-sensitive cultivated tomato (Solanum lycopersicum L.) breeding line and a chilling-tolerant inbred accession of the tomato wild species S. pimpinellifolium L. Screening of the fruit of 148 RILs under cold storage (1.5°C) indicated presence of significant variations in chilling tolerance, manifested by varying degrees of fruit injury. Two extremely contrasting groups of RILs were identified, chilling-tolerant and chilling-sensitive RILs. The RILs in the two groups were further investigated under chilling stress conditions, and several physiological parameters, including weight loss, chlorophyll fluorescence parameters Fv/Fm, and Performance Index (PI), were determined to be efficient markers for identifying response to chilling stress in postharvest fruit. The Fv/Fm values reflected the physiological damages endured by the fruit after cold storage, and PI was a sensitive marker for early changes in photosystem II function. These two parameters were early indicators of chilling response before occurrence of visible chilling injuries. Antioxidant activities and ascorbic acid content were significantly higher in the chilling-tolerant than the chilling-sensitive lines. Further, the expression of C-repeat/DREB binding factors (CBFs) genes swiftly changed within 1-hr of fruit exposure to the chilling temperature, and the SlCBF1 transcript level was generally higher in the chilling-tolerant than chilling-sensitive lines after 2-hr exposure to the low temperature. This research demonstrates the presence of potential genetic variation in fruit chilling tolerance in the tomato RIL population. Further investigation of the RIL population is underway to better understand the genetic, physiological, and biochemical mechanisms involved in postharvest fruit chilling tolerance in tomato.